The Re-discovery of live populations of Cnemaspis tropidogaster (Boulenger, 1885) (Sauria, Gekkonidae) from Sri Lanka after 120 years - Amarasinghe, A.a. Thasun; Campbell, Patrick D.; Madawala, Majintha B.; Botejue, W. Madhava S.; Gabadage, Dinesh E.; Silva, Anslem De; Karunarathna, D.m.s. Suranjan (Zootaxa, 2016)
Gonatodes kandianus var. tropidogaster was described by Boulenger (1885) with only “Ceylon” (=Sri Lanka) as its locality. This taxon was later assigned to the genus Cnemaspis and then recorded from many different parts of the country. Misleading taxonomic publications and muddled nomenclatural issues has since rendered its taxonomic position unclear. Recent studies have revealed, however, that C. tropidogaster is a species complex, and the species and its types have been redescribed. Unfortunately, no live populations of this species have been recorded until now. Here we report the rediscovery of live populations of this species 120 years after its last collection date records. C. tropidogaster was rediscovered from a low elevation (50–80 m asl.) of the wet zone of Sri Lanka. The rediscovered population was attributed to C. tropidogaster on the basis of a suite of matching morphometric and meristic characters that distinguish C. tropidogaster from other Sri Lankan Cnemaspis.